2021
DOI: 10.3390/biom11020246
|View full text |Cite
|
Sign up to set email alerts
|

Initial Identification of UDP-Glucose Dehydrogenase as a Prognostic Marker in Breast Cancer Patients, Which Facilitates Epirubicin Resistance and Regulates Hyaluronan Synthesis in MDA-MB-231 Cells

Abstract: UDP-glucose-dehydrogenase (UGDH) synthesizes UDP-glucuronic acid. It is involved in epirubicin detoxification and hyaluronan synthesis. This work aimed to evaluate the effect of UGDH knockdown on epirubicin response and hyaluronan metabolism in MDA-MB-231 breast cancer cells. Additionally, the aim was to determine UGDH as a possible prognosis marker in breast cancer. We studied UGDH expression in tumors and adjacent tissue from breast cancer patients. The prognostic value of UGDH was studied using a public Kap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 62 publications
0
24
1
Order By: Relevance
“…UGDH may induce resistance to chemotherapy via drug elimination. This was supported by a recent study demonstrating that high levels of UGDH are correlated with worse prognosis in triple‐negative breast cancer patients receiving chemotherapy, likely by promoting UDP‐GlcA‐mediated detoxification and elimination of epirubicin [ 76 ]. The effect of UGDH on SNAI1 supports that UGDH has a regulatory role in EMT and that its function may exceed its catalytic role, perhaps via nonconventional signalling regulatory effects such as glycosylation (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…UGDH may induce resistance to chemotherapy via drug elimination. This was supported by a recent study demonstrating that high levels of UGDH are correlated with worse prognosis in triple‐negative breast cancer patients receiving chemotherapy, likely by promoting UDP‐GlcA‐mediated detoxification and elimination of epirubicin [ 76 ]. The effect of UGDH on SNAI1 supports that UGDH has a regulatory role in EMT and that its function may exceed its catalytic role, perhaps via nonconventional signalling regulatory effects such as glycosylation (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…Intracellular glucose levels were unchanged across all R7 modulations and not detected in MRBC cell lines, but lactate levels were significantly reduced upon RON or β-catenin loss not with DEK loss ( Fig 1C ). An alternative utilization of glucose for glycogen synthesis and the addition of glucose to other biomolecules involves uridine diphosphate (UDP) conjugation of glucose, which is implicated in supporting breast cancer migration, metastasis, and treatment resistance [ 28 , 29 ]. UDP-glucose levels were ablated upon DEK loss ( Fig 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the processes controlled by this natural barrier are the modulation of immune effectors (35,113), the inhibition of diffusion of chemotherapeutic drugs (128) and the difficult uptake of DNA transgene complexes in gene therapy (129). Furthermore, previous studies from our laboratory and other authors have shown that ECM components play important roles in acquired resistance to anticancer drugs (34,130,131). Therefore, the development of novel cancer treatments that target HA by altering the ECM represents a pioneering approach to the treatment of several cancers.…”
Section: -Mu Treatment As a New Strategy Of Co-adjuvant Drug On Conventional Antineoplastic Therapiesmentioning
confidence: 99%